Monostotic Fibrous Dysplasia of the Mandible in a 9-Year-Old Male Patient Treated with a Conservative Surgical Treatment: A Case Report and 15-Year Follow-Up - Antoine Berberi; Georges Aoun; Emile Khalaf; Georges Aad (Hindawi Limited, 2021)
Fibrous dysplasia is a developmental disorder of the bone that originates from a genetic defect disturbing the osteogenesis leading to the replacement of normal bone with the excess proliferation of fibrous tissue. It can be associated with hyperpigmentation of the skin and endocrine disorders. Fibrous dysplasia can manifest in a monostotic form affecting one bone or in a polyostotic form involving several bones. Approximately 30% of monostotic forms are observed in the maxilla and the mandible. It frequently appears in the posterior region and is usually unilateral. It is found in teenagers and could become static after adulthood. Patients can present with swelling, facial asymmetry, pain, or numbness on the affected side. Treatment modalities vary between conservative surgical treatment, radical surgical approach, and medical treatment based on bisphosphonates. Here, we present a case of a monostotic form of fibrous dysplasia affecting the posterior left region of the mandible in a 9-year-old male complaining of gradually increased swelling on the left mandibular side of one-year duration. The diagnosis of fibrous dysplasia is established based on clinical, radiographical, and histopathological features. Conservative surgery is implemented with surgical shaving and reencountering of the bone excess to reduce the facial asymmetry. Recurrence is reported 10 years later and is also treated with a localized osteoplasty and remodeling of the bone contours. Five years later, the lesion remains stable. In conclusion, a conservative approach should be adopted as the first line of treatment for young patients suffering from monostotic fibrous dysplasia.